Competition In Classroom Activities To Enhance Students’ Communicative Competence - Ningtyas, Tutik Ratna; Amirudin, Amirudin (Wistara: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This study is a class action research study which is aimed to find out how the competition in classroom activities in relation with communicative competence can be conducted properly. Communicative competence as the ability to utilize both knowledge and skills of a language to communicate appropriately by involving social and cultural context is an essential competence which should be mastered by English learners, especially in college level. Mastering communicative competence means having capacity in four areas of the competence namely grammatical competence, sociolinguistics competence, discourse competence and strategic competence. In achieving this goal of learning, the synergy among strategy, method and learning instruments is a must. The synergy of the mentioned parts of teaching and learning activity then should be presented in effective classroom activities. Classroom activities should be designed to encourage students to perform their communicative competence. Collaborating students and teachers’ roles to trigger students’ motivation to develop themselves by competing in healthy environment is a movement to help students enhancing their communicative competence. The researchers use qualitative approach. The result shows that healthy competition can elevate students’ communicative competence.